To determine whether the equation \((4\sqrt{3})^{24}(3\sqrt{6}) = (4^3)^5\) is true, we can simplify both sides of the equation.
- Left Side:
- \((4\sqrt{3})^{24} = (4 \cdot 3^{1/2})^{24} = 4^{24} \cdot (3^{1/2})^{24} = 4^{24} \cdot 3^{12}\)
- \((3\sqrt{6})^{6} = (3 \cdot 6^{1/2})^{6} = 3^6 \cdot (6^{1/2})^{6} = 3^6 \cdot 6^{3} = 3^6 \cdot (2 \cdot 3)^{3} = 3^6 \cdot 2^{3} \cdot 3^{3} = 2^3 \cdot 3^{9}\)
Combining the left side gives us:
- \(4^{24} \cdot 3^{12} \cdot 2^3 \cdot 3^{9} = 4^{24} \cdot 2^3 \cdot 3^{21}\)
- Right Side:
- \((4^3)^5 = 4^{15}\)
Now we can compare both sides:
- Left Side: \(4^{24} \cdot 2^3 \cdot 3^{21}\)
- Right Side: \(4^{15}\)
Final Analysis: The left side clearly does not equal the right side based on the exponents of 4 alone, and since the left side has additional factors, we conclude that the equation is False.
Thus, the correct response is:
False. The Quotient Property has not been applied correctly.